HISTORICAL AND CULTURAL HERITAGE OF BUNDELKHAND REGION CONSERVATION, VISUALIZATION, USING G.I.S TECHNOLOGIES - Verma , Ashish; Devi, Artti (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research paper investigates the conservation, visualization, and study of Bundelkhand’s historical and cultural heritage using Geographic Information Systems (GIS) technologies. Located in central India, Bundelkhand is renowned for its rich historical sites, including ancient temples, forts, and palaces. These sites face significant preservation challenges due to environmental degradation, neglect, and socio-economic constraints. This study explores the application of GIS technologies in documenting, analyzing, and visualizing Bundelkhand’s heritage. GIS offers powerful tools for creating detailed inventories, assessing the physical condition of structures, monitoring changes, and enhancing public engagement through immersive visualizations. The paper highlights the transformative potential of GIS in heritage conservation through case studies of the Khajuraho temples and the Orchha Fort Complex, demonstrating how GIS facilitates comprehensive documentation, condition assessment, and informed conservation strategies. While GIS technologies present numerous benefits, such as enhanced data integration and improved spatial analysis, challenges related to data accuracy, technical expertise, and resource constraints must be addressed. The study underscores the need for a balanced approach that combines traditional conservation methods with advanced GIS technologies to ensure the sustainable preservation of Bundelkhand’s cultural legacy. By leveraging GIS, conservationists, researchers, and policymakers can safeguard Bundelkhand’s heritage, promote sustainable tourism, and foster a deeper appreciation for the region’s rich cultural history. This research contributes to the broader discourse on digital transformation in heritage conservation, emphasizing the critical role of GIS in preserving and promoting cultural heritage in the digital age.